O consensualismo e a arbitragem comercial - Sirotsky Scaletscky, Fernanda (2019)
Arbitration is a consensual and private dispute resolution mechanism which leads to an enforceable arbitral award. In commercial arbitration the agreement to arbitrate is considered to be the cornerstone of arbitration, and that is why this study will be centered in it. Being the arbitration agreement a contract and considering that for the formation of any valid contract the presence of consent is required, whereby the mutual will of the parties is enough to the conclusion of the contract, the consent shows itself as an essential element of the agreement to arbitrate, since it doesn’t exist without the mutual will of the parties. In this sense, it is necessary to examine how consent applies and manifests itself in commercial arbitration. To that end, the issues concerning the application of consent in the formal and material validity of the agreement to arbitrate must be developed. With regard to the formal requirements for the validity of the arbitration convention, it will be seen that even if they have been relativized, especially in relation to international commercial arbitration, many questions still arise about the need to respect the formal requirements in order to a party may be considered validly bound by the arbitration agreement, this is so in Brazilian law and in many other jurisdictions. Regarding the substantial validity of the agreement to arbitrate, this study will examine other forms of manifestation of consent, considering that the expression of the will of the parties is not always proven by their express signature in the written arbitration agreement, and the behaviors adopted by the parties, from the beginning to the termination of the contract, and even during the arbitral proceedings, may be a way of pointing to their real intentions in relation to arbitration. In the end, it will be made a critical reflection in order to verify what is the importance of consent in current arbitration practice and if its concept has changed, in order to embrace the new practices adopted by the players of international trade. Keywords: Consent. Agreement to arbitrate. Contract. Applicable law. Formal and material validity.